Ruins of Empire or Tears of Joy?: An Intersection of History and the Bible in Lope de Vega’s Religious Comedias - Vangshardt, Rasmus (Journal of the bible and its reception, 2024)
This article studies a way in which Lope de Vega used biblical theatre as a vehicle for historiographical interpretation. The article does so by situating elements from a number of Lope’s religious comedias in the context of what has recently been described as Golden Age Spain’s "aesthetic-historical culture." The study begins with an analysis of intersections of history and the Bible in Lope’s La hermosa Ester . The second half comprises a reconstruction of the role of the Bible in Lope’s poetics. Via this two-pronged strategy, the article makes a case for seeing a feature of Lope’s biblical comedias as part of said aesthetic-historical culture of early modern Spain and proposes a way to understand the historiographical profile of Lope’s biblical drama. This leads to the claim that Lope’s biblical drama effectively contributed to the attribution of a new generic mixture to understandings and interpretations of the course of history itself. This interpretation invites a highly open-ended approach to the end of time between ruin and redemption.